KONTRIBUSI ZAKAT INFAK SEDEKAH DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT MISKIN PADA BAZNAS DI KOTA JAMBI - Puteri Desparansa (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the contribution of zakat infaq and sedekah to improve the economy of the poor at BAZNAS Jambi City, how is BAZNAS’s strategy in distributing zakat funds, what are the inhibiting factors and what efforts can be made to improve the economy of the poor in Jambi city. Sources of data used are primary and secondary data sources using techniques and data collection tools through interviews and documentation. The results of this study indicate that the zakat management carried out by BAZNAS Jambi City is consumptive and productive, with a percentage of 30% for consumptive and 70% for productive, but in Jambi City 30% is considered productive while for consumptive it reaches 70% because the people in Jambi City are currently This priority prioritizes short-term needs such as assistance in the form of basic necessities, educational assistance and cash compensation. In distributing productive zakat, Jambi City BAZNAS currently uses a grant contract where zakat funds distributed to mustahik are given free of charge without being returned on condition that they must commit to what is given.